Categories and contexts anthropological and historical studies in critical demography - Szreter, Simon; Sholkamy, Hania; Dharmalingam, A.; Oxford eBooks; International Union for the Scientific Study of Population (Oxford : Oxford University Press, 2004)
Demographers tend to analyse population issues scientifically through sets of fixed social categories that are divorced from dynamic relationships and local contexts and processes. This volume questions these fixed categories.
Papers from the IUSSP seminar in Cairo, September 1999.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Demography -- Congresses; Electronic books